Characterization and evaluation of Bacillus subtilis GYUN-2311 as a biocontrol agent against Colletotrichum spp. on apple and hot pepper in Korea - Heo, Yunjeong; Lee, Younmi; Balaraju, Kotnala; Jeon, Yongho (Frontiers in Microbiology, 2024)
Crop plants are vulnerable to a variety of diseases, including anthracnose, caused by various species of Colletotrichum fungi that damages major crops, including apples and hot peppers. The use of chemical fungicides for pathogen control may lead to environmental pollution and disease resistance. Therefore, we conducted this research to develop a Bacillus subtilis-based biological control agent (BCA). B. subtilis GYUN-2311 (GYUN-2311), isolated from the rhizosphere soil of an apple orchard, exhibited antagonistic activity against a total of 12 fungal pathogens, including eight Colletotrichum species. The volatile organic compounds (VOCs) and culture filtrate (CF) from GYUN-2311 displayed antifungal activity against all 12 pathogens, with 81% control efficiency against Fusarium oxysporum for VOCs and 81.4% control efficacy against Botryosphaeria dothidea for CF. CF also inhibited germination and appressorium formation in Colletotrichum siamense and C. acutatum. The CF from GYUN-2311 showed antifungal activity against all 12 pathogens in different media, particularly in LB medium. It also exhibited plant growth-promoting (PGP) activity, lytic enzyme activity, siderophore production, and the ability to solubilize insoluble phosphate. In trials on apples and hot peppers, GYUN-2311 effectively controlled disease, with 75% and 70% control efficacies against C. siamense in wounded and unwounded apples, respectively. Similarly, the control efficacy of hot pepper against C. acutatum in wounded inoculation was 72%. Combined application of GYUN-2311 and chemical suppressed hot pepper anthracnose to a larger extent than other treatments, such as chemical control, pyraclostrobin, TK®, GYUN-2311 and cross-spraying of chemical and GYUN-2311 under field conditions. The genome analysis of GYUN-2311 identified a circular chromosome comprising 4,043 predicted protein-coding sequences (CDSs) and 4,096,969 bp. B. subtilis SRCM104005 was the strain with the highest average nucleotide identity (ANI) to GYUN-2311. AntiSMASH analysis identified secondary metabolite biosynthetic genes, such as subtilomycin, bacillaene, fengycin, bacillibactin, pulcherriminic acid, subtilosin A, and bacilysin, whereas BAGEL analysis confirmed the presence of competence (ComX). Six secondary metabolite biosynthetic genes were induced during dual culture in the presence of C. siamense. These findings demonstrate the biological control potential of GYUN-2311 against apple and hot pepper anthracnose.